The effect of wash treatment on the mechanical properties and energy absorption potential of a 3D printed polymethyl methacrylate (PMMA). (March 2021) - Bardelcik, Alexander; Yang, Steven; Alderson, Faraz; Gadsden, Andrew
Graphical abstract: Highlights: Tensile specimens were 3D printed (SLA) and washed with 13 different solutions consisting of Isopropyl Alcohol, Hydrogen Peroxide and Detergent. Tensile tests showed that the wash solutions significantly modified the peak stress, elongation and toughness of the PMMA polymer. FE simulations of octet-truss lattice structure compression tests were developed using the measured tensile properties as input. The models revealed that a 5% hydrogen peroxide and detergent (HP5+D) and a full detergent wash resulted in desirable energy absorption behavior. Abstract: Stereolithographic 3D-printing of a Polymethyl Methacrylate (PMMA) resin was used to manufacture miniature dog-bone specimens that were subject to a variety of wash treatments consisting of Isopropyl Alcohol (IP), Hydrogen Peroxide (HP) and a Detergent (D) solution. The washed dog-bone specimens were then tested in uniaxial tension and the mechanical properties were quantified to assess the potential use of the resultant materials for the design of energy absorbing lattice structures. Compared to an As-Printed material, a detergent wash treatment resulted in almost no loss in peak stress, but a 61 % increase in toughness due to enhanced elongation. Moderate decreases in peak stress and high elongation were observed for HP washes. A 5 % (concentration) HP wash with detergent (HP5 + D) resulted in a 90 % greater toughness than the As-Printed material. Isopropyl washed specimens showed low toughness due to low peak stresses. A finite element study was conducted to simulate compression tests of an octet-truss lattice structure for which the tensile test properties were used as model inputs. The simulations revealed some relationships between the predicted energy absorption-tensile properties and showed that the HP5 + D (moderate peak force) and As-Printed + D (high peak force) washed conditions have potential application as energy absorbing octet-truss lattice structures.